Perbandingan Hasil Pemeriksaan Glukosa Urin Segar dan Urin Tunda Dua Jam pada Penderita Diabetes Melitus Metode Carik Celup - Yulianti Yulianti; Nahir Bandu; Suharsih Thahir (Jurnal Media Laboran, 2018)
Urine comes from blood that is filtrated by glumelurus and then secreted, diabsorsi and excreted through the urinary tract. This urine glucose test aims to determine the difference in the results of both the immediate and delayed two-hour examination in diabetic mellitus patients. The study was conducted in a quasi-experimental manner. The study was intended to look at the differences in the results of fresh urine glucose and urine delayed by two hours in diabetic mellitus patients. With accidental sampling sampling techniques. The sign test results show that n '- t1 = 15> T = 0 at the confidence level of 0.05 in this case Ho is accepted means that there is no significant difference between the results of fresh urine glucose examination and urine delayed by two hours in diabetic patients with dipstick method. Based on the results of the above research, it is recommended that a two-hour delay in urine can be used for urinary glucose examination but the urine examination should be a good examination material is a urine sample that has just been cleared because the urine delayed by the examiner can affect the results of other tests.